Amylose content preference for cooked milled rice among filipino consumers in non-irrigated lowland ecosystems - Felix, Angelina dR.; Roferos, Leslie T.; Bandonill, Evelyn H.; Juliano, Bienvenido O. (2007)
Rice quality preference is well defined in the irrigated lowland ecosystem but not in adverse ecosystems. The cooked milled form of four modern rice varieties of different amylose content (AC) - NSIC Rd04, PSB Rc96, IR64 and PSB Rc72H - was subjected to sensory evaluation by a consumer panel in selected Philippine barangays representative of cool elevated, rainfed lowland, upland and saline prone ecosystems to define quality preferences of consumers for the rice varieties. PSB Rc72H consistently had the highest acceptability and preference ranked scores, indicating consumer preference for soft, aromatic rice in all four ecosystems. In the cool elevated and rainfed areas, rice with low amylose content (AC) and low gelatinization temperature (GT) and which had softer texture, typified by PSB Rc72H, was the quality type preferred, although the japonica-type rice variety NSIC Rc104 had a positive preference ranked score but only among consumers in the cool elevated area. Upland and saline area consumers preferred rices of moderately tender to soft texture such as IR64 and PSB Rc72H, which had 18% AC with low GT, to 25% AC with intermediate GT. The study confirmed the more general consumer preference for aged 18-22% AC rice across ecosystems, but suggested a specific breeding objective toward an 18-25% AC with intermediate GT for rice varieties in the upland and saline ecosystems, and toward ≤18% AC and low GT for japonicatype rices in the cool elevated area.
Keywords: Rice quality; Consumer preferences